An introduction to human geography : (Pearson / Prentice Hall, 2004)
An introduction to Human Geography provides a comprehensive overview of the major topics within human geography, including settlements, population, resources, the economy, consumption, citizenship, culture, society, the politics of place and globalisation. Coherent and substantial chapters ensure balanced treatment across the field of human geography.